BONE HEALTH AND GROWTH IN SPINAL MUSCULAR ATROPHY TYPE 2 AND 3 - Osman Kipoğlu; Esin Karakılıç Özturan; Orhan Coşkun; Ayşe Pınar Öztürk; Edibe Pembegül Yıldız; Firdevs Baş; Nur Aydınlı; Meliha Mine Çalışkan (İstanbul Tıp Fakültesi Dergisi)
Objective: Spinal muscular atrophy is a lower motor neuron disease, but other parts of the body could be affected. This study compared bone mineral density with bone metabolism and physical growth rates in patients diagnosed with spinal muscular atrophy type 2 and type 3. Material and Methods: Twenty-six patients with spinal muscular atrophy were included in the study (15 patients for type 2 and 11 for type 3). Weights and heights of patients were measured, standard deviation scores were determined, and the body-mass index was calculated. Motor function and pubertal assessment were performed. Serum calcium, phosphorus, alkaline phosphatase, parathormone, and 25-hydroxyvitamin vitamin D levels were compared. Spine radiography for scoliosis and bone densitometry for bone mineral density were performed, and volumetric bone mineral density was calculated for age and sex. Results: Medians of height standard deviation scores were significantly lower in type 2 patients. There was no difference between the two groups in terms of serum calcium, phosphorus, alkaline phosphatase, parathormone, and 25-hydroxyvitamin D levels. The ratio of scoliosis was higher in type 2 patients as was its severity, but Z-scores of volumetric bone mineral density was lower in the same group. Conclusion: This study showed that bone mineralization and growth rates were significantly lower in spinal muscular atrophy, mainly in type 2. Further studies are needed to evaluate bone health in spinal muscular atrophy patients.